Neopterin and alpha and beta interleukin-1 levels in sera of patients with human immunodeficiency virus infection. - Reddy, M M (1989)
Levels of neopterin and alpha and beta interleukin-1 (IL-1) in sera of normal controls, asymptomatic intravenous drug abusers, homosexuals, and patients with lymphadenopathy or acquired immunodeficiency syndrome were measured. Neopterin levels were elevated in the sera of human immunodeficiency virus (HIV)-seronegative intravenous drug abusers and homosexuals, as well as in the sera of HIV-seropositive patients. Alpha IL-1 was the most predominant form of IL-1 found in the sera of all groups, and its level in HIV-seronegative intravenous drug abusers was elevated compared with the level in controls, whereas its levels in asymptomatic HIV-seropositive intravenous drug abusers and asymptomatic HIV-seronegative and HIV-seropositive homosexuals were decreased relative to the level in controls. Beta IL-1 levels in sera in all groups were not significantly different from the control value, except for the HIV-seropositive homosexual group; in this group the beta IL-1 level was significantly decreased compared with the control value.